Uncommon differential diagnosis of a breast ulcer: a case study. (2nd September 2021) - Combi, Francesca; Papi, Simona; Marchesini, Denise; Andreotti, Alessia; Gambini, Anna; Palma, Enza; Tazzioli, Giovanni
Abstract : Introduction: Spider bites are common worldwide. Frequently symptoms resolve without any adverse outcome, but in rare cases the bite can cause severe morbidity. The most typical presentation of Mediterranean recluse spider ( Loxosceles Rufescens ) bite is a dermatonecrotic lesion of the skin (skin loxoscelism). When the only manifestation of a spider bite is an ulcerated skin lesion, clinical suspicion and differential diagnosis strongly depend on its site. We present the case of an ulcerated wound of the breast, diagnosed as a Mediterranean recluse spider bite. Case presentation: A 79-year-old woman presented a 10cm-wide soft tissue ulceration of her left breast. At first, the diagnostic hypothesis of an ulcerated cancer was ruled out. Two family members revealed a recent history of Mediterranean recluse spider bite and the same clinical diagnosis was made for our patient. A wide excision was performed, with complete resolution of symptoms. Discussion: No specific diagnostic criteria for spider bites are available. Diagnosis is usually clinical. Skin loxoscelism could be easily mistaken for cellulitis, various types of skin infections, cutaneous anthrax, vasculitis, scorpion sting, pyoderma gangrenosum, erythema migrans of Lyme disease or prurigo nodularis. A thorough anamnestic interview is fundamental to raise the diagnostic hypothesis. When possible, a biopsy is recommended and it is extremely important when the ulcer can mimic a cancer, as is the case in breast tissue. Conclusion: We recommend a wide excision of the wound after failure of conservative treatment, in order to obtain local control and to perform histological examination on a more representative specimen.